2021
DOI: 10.21037/jtd-20-2896
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term clinical outcomes between robot- assisted minimally invasive esophagectomy and video-assisted minimally invasive esophagectomy: a systematic review and meta-analysis

Abstract: Background: Though robot-assisted minimally invasive esophagectomy (RAMIE) is demonstrated to offer a better visualization and provide a fine dissection of the mediastinal structures to facilitate the complex thoracoscopic operation, the superiorities of RAMIE over MIE have not been well verified. The aim of this study was to explore the actual superiorities through comparing short-term results of RAMIE with that of MIE. Methods: PubMed, EMBASE and web of science databases were systematically searched up to Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Robotic approach seemed to be superior to conventional laparoscopy in terms of oncologic outcomes (mean number of harvested nodes obtained, p = 0.001) and postoperative complications (incidence of pneumonia after surgery, p = 0.003). Even in this case robotic surgery has the only disadvantage of operative time (shorter in the laparoscopic group, p = 0.003), but this data was not associated with increased postoperative morbidities.Our results are in accordance with the results of the meta-analysis by Zheng et al [ 71 ] in terms of longer operative time in the robotic group. Similarly pneumonia rate was lower in the robotic group, and this data has been confirmed by our analysis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Robotic approach seemed to be superior to conventional laparoscopy in terms of oncologic outcomes (mean number of harvested nodes obtained, p = 0.001) and postoperative complications (incidence of pneumonia after surgery, p = 0.003). Even in this case robotic surgery has the only disadvantage of operative time (shorter in the laparoscopic group, p = 0.003), but this data was not associated with increased postoperative morbidities.Our results are in accordance with the results of the meta-analysis by Zheng et al [ 71 ] in terms of longer operative time in the robotic group. Similarly pneumonia rate was lower in the robotic group, and this data has been confirmed by our analysis.…”
Section: Discussionsupporting
confidence: 93%
“…More recently, Robot-Assisted Minimally Invasive Esophagectomy (RAMIE) was introduced as an alternative minimally invasive method which may allow improved view of thoracic structures and increased precision [ 69 ]. Nevertheless, the presumed advantages of the robotic surgery are still under debate [ 69 , 70 , 71 ]. In this setting, three meta-analysis tried to assess if the robotic approach could be considered the best treatment to the esophageal cancer [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, several other studies have also confirmed the same results, reporting that robotic surgery showed better performance in dissection along the RLN nodes than thoracoscopic surgery [ 12 , 18 , 30 , 31 ]. Other researchers reported a reduced incidence of RLN palsy after robotic surgery, which may be another advantage of robotic esophagectomy [ 32 - 34 ]. Zheng et al [ 34 ] also documented a lower incidence of vocal cord palsy in the robotic surgery group in their meta-analysis.…”
Section: Discussionmentioning
confidence: 99%